Measurement Methods to Evaluate Engineered Nanomaterial Release from Food Contact Materials. Issue 4 (July 2014) - Noonan, Gregory O.; Whelton, Andrew J.; Carlander, David; Duncan, Timothy V.
Abstract This article is one of a series of 4 that report on a task of the NanoRelease Food Additive project of the Intl. Life Science Inst. Center for Risk Science Innovation and Application to identify, evaluate, and develop methods that are needed to confidently detect, characterize, and quantify intentionally produced engineered nanomaterials (ENMs) released from food along the alimentary tract. This particular article focuses on the problem of detecting ENMs that become released into food indirectly from food contact materials. In this review, an in‐depth analysis of the release literature is presented and relevant release mechanisms are discussed. The literature review includes discussion of articles related to the release phenomenon in general, as experimental methods to detect ENMs migrating from plastic materials into other (nonfood) complex matrices were determined to be relevant to the focus problem of food safety. From the survey of the literature, several "control points" were identified where characterization data on ENMs and materials may be most valuable. The article concludes with a summary of findings and a discussion of potential knowledge gaps and targets for method development in this area.